Percy Jackson an the Olympians : Wrath of the Triple Goddess - Book 7 - Riordan, Rick ([New York] : Disney Hyperion, 2024)
"In his continuing quest to earn college recommendation letters from the gods, Percy has to pet sit the goddess Hecate's polecat and giant mastiff during Halloween week. What could go wrong?"--
Keywords: Jackson, Percy -- (Fictitious character) -- Juvenile fiction; Hecate -- (Greek deity) -- Juvenile fiction; Jackson, Percy -- (Fictitious character) -- Fiction; Hecate -- (Greek deity) -- Fiction; Mythology, Greek -- Juvenile fiction; Goddesses -- Juvenile fiction; Pet sitting -- Juvenile fiction; Animals -- Juvenile fiction; Monsters -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Fantasy fiction; Mythology, Greek -- Fiction; Goddesses -- Fiction; Pet sitting -- Fiction; Animals -- Fiction; Monsters -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Fantasy fiction; Action and adventure fiction